Investigating Maternal Touch and Infants' Self‐Regulatory Behaviours during a Modified Face‐to‐Face Still‐Face with Touch Procedure. Issue 6 (5th June 2014) - Jean, Amélie D. L.; Stack, Dale M.; Arnold, Sharon
<x xml:space="preserve">Abstract</x> Maternal touch and infants' self‐regulatory behaviours were examined during a modified Still‐Face with Touch (SF + T) procedure. Mothers and their 5½‐month‐old infants participated in one period of Normal interaction followed by three SF + T periods. Maternal functions of touch, and infants' self‐regulatory behaviour, affect, and attention were evaluated. Contrary to a typical SF procedure, the amount of smiling remained high while fretting remained low. High levels of maternal touching and variations in the functions of maternal touch were observed across periods. Playful touch remained high while there was an increase in nurturing touch and a decrease in attention‐getting touch from the Normal to all SF + T periods. Similar amounts of self‐regulatory behaviours were observed across periods with the exception of a decrease in bidirectional exchanges during the SF + T periods. Finally, across periods, maternal touch and infants' self‐regulatory behaviours were found to be temporally organized with infants' affect and attention. Examining how mothers use touch when other forms of communication are absent increased our understanding of the role of touch in infants' emotion regulation. Copyright © 2014 John Wiley & Sons, Ltd.